Acute Dystonia Caused by Clomipramine: a Case Report - Baykara, Sema; Tabara, Muhammed Fatih; Korkmaz, Sevda; Atmaca, Murad (Yerkure Tanitim & Yayincilik Hizmetleri A S, 2018)
Drug-induced acute dystonia is a movement disorderthat occurs most often with neuroleptics, though there are many drugs in its etiology. The exact mechanism of antidepressant-associated extrapyramidal side effects (EPS) is not known. However, hypotheses including inhibition of dopaminergic function in the nigrostriatal pathway, impaired balance between dopaminergic, serotonergic, noradrenergic or cholinergic activity, and serotonergic inhibition of dopaminergic functions in the striatum leading to extrapyramidal side effects have been suggested. The number of cases with acute dystonia during clomipramine use is low. We wish to draw attention to this rare side effect of clomipramine and to contribute to the literature by presenting a case of acute dystonia on the 5th day of clomipramine treatment in a 19-year-old male patient.
Keywords: Antidepressants; clomipramine; dystonia